Mind and Cosmos. Why the Materialist Neo-Darwinian Conception of Nature is Almost Certainly False - Franz Magnis-Suseno (Jurnal Teologi (Journal of Theology), 2020)
Mind and Cosmos. Why the Materialist Neo-Darwinian Conception of Nature is Almost Certainly False